Interactive effects of prenatal alcohol exposure and chronic stress in adulthood on anxiety-like behavior and central stress-related receptor mRNA expression: Sex- and time-dependent effects. (November 2018) - Lam, Vivian Y.Y.; Raineki, Charlis; Ellis, Linda; Yu, Wayne; Weinberg, Joanne
Highlights: Prenatal alcohol exposure (PAE) increased anxiety-like behavior in males and females. PAE differentially altered GR mRNA in males and females. PAE and CUS interact to unmask alterations in GR and CRHR1 mRNA expression in males. PAE and CUS interact to unmask alterations in MR mRNA expression in females. Abstract: Children and adults prenatally exposed to alcohol show higher rates of mental health problems than unexposed individuals, with depression and anxiety being among the more commonly encountered disorders. Previous studies in rats showed that prenatal alcohol exposure (PAE) can indeed increase depressive- and anxiety-like behavior in adulthood; however, depression and anxiety are often observed in the context of stress and/or a dysregulated stress response system (the hypothalamic-pituitary-adrenal [HPA] axis). PAE can dysregulate the HPA axis, resulting in hyperresponsivity to stress. In turn, this may predispose individuals prenatally exposed to alcohol to the adverse effects of stress compared to unexposed individuals. We have shown previously that PAE animals may be more sensitive to the effects of chronic stress on behavior, showing increased anxiety- and depressive-like behavior following chronic unpredictable stress (CUS) exposure. Here, we investigated the independent and interactive effects of PAE and adult CUS on anxiety-like behavior and receptor systems (corticotropin-releasing hormone receptor type 1 [CRHR1], mineralocorticoid receptor [MR], and glucocorticoid receptor [GR]), and underlying stress and emotional regulation, and whether exposure to CUS differentially results in immediate or delayed effects. Adult male and female offspring from PAE, pair-fed (PF), and ad libitum -fed control (C) dams were exposed to either 10 days of CUS or left undisturbed. Behavioral testing began 1 or 14 days post-CUS, and brains were collected following testing. Anxiety-like behaviors were evaluated using the open field, elevated plus maze and dark-light emergence tests. CRHR1, MR, and GR mRNA expression were assessed in the medial prefrontal cortex (mPFC), amygdala, and hippocampal formation, brain areas key to both stress and emotional regulation. We found that PAE differentially increased anxiety-like behavior and altered GR mRNA in males and females compared to their control counterparts. Furthermore, depending on the timing of testing, CUS unmasked alterations in GR and CRHR1 mRNA expression in the mPFC and amygdala in PAE males, and MR mRNA in the hippocampal formation in PAE females compared to their C counterparts. Overall, the changes observed in these receptor systems may underlie the increase in anxiety-like behavior following PAE and CUS exposure in adulthood. That CUS differentially affected brain and behavioral outcome of PAE and C animals, and did so in a sexually-dimorphic manner, has important implications for understanding the etiology of psychopathology in individuals prenatally exposed to alcohol.